The Outsourcing Bogeyman. - Drezner, Daniel W. (Foreign Affairs)
The election-year pronouncements of politicians and commentators have it that the outsourcing of U.S. jobs to other countries is now a very serious problem, but such alarmism is misguided. In reality, outsourcing provides many more advantages than disadvantages, both now and in the longer term. Critics of outsourcing are correct to point out that the movement of jobs offshore deserves attention and that some measures to help affected workers are required, but if their overhyped warnings manage to provoke protectionist responses from lawmakers, they will do much more harm than good to the U.S. economy and to the U.S. workers they purport to defend.